Validity of Assessment Instruments Based on Higher-Order Thinking Skill on Learning Pendidikan Pancasila dan Kewarganegaraan - Pebriyenni, Pebriyenni; Muslim, Muslim; Sumarni, Sumarni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aims to develop a valid Higher Order Thinking Skill based assessment instrument on Pancasila and Civic Education subjects in Grade XI Senior High School. The assessment instrument developed is limited to basic competence 3.1 analyzing cases of human rights violations in the perspective of Pancasila in order to realize the harmony of human rights and obligations in the life of the nation and state. The type of this study is research and development. The development design model used is the Plomp model by dividing the research phase into three phases, namely preliminary research, prototyping phase, and assessment phase. This research was conducted up to prototyping phase. This stage is used to see the validity of the HOTS-based Civics subject assessment instrument. The study was done at Bung Hatta University and validated by three experts (validator). The results showed that the validity level of the instrument from the material aspect was 82.66%, the instrument construction validity was 86.00%, the HOTS assessment instrument validity from the language aspect and additional rules were 84.33% for language and 85.33% for additional rules. Thus the average validation of the HOTS assessment instrument is 84.58%. It can be concluded that the HOTS assessment instrument in PPKn subjects has the validity criteria of valid and can be used with minor revisions. It is recommended to continue on the practicality and effectiveness of the instrument.